Tarekat dan Gerakan Sosial Keagamaan Shaykh Hasan Maksum - Ja?far, Ja?far (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
The article scrutinizes the tarekat (Sufi order) and the social-religious movement of Shaykh Hasan Maksum, a less noticeable Sufi figure within the literatures of tasawuf Nusantara but was an important figure who played essential roles and had great influence within the dynamic of social-religious aspects in East Sumatera. As a mufti-sufi, Shaykh Hasan was a prominent figure within literatures of religious knowledge, mainly theology, fiqh, and Sufism, and had greater influence than other Sufi figures in East Sumatera. It has been a result of his ?religious authority?, which covered the entire sultanate?s sway in this region at that time. Shaykh Hasan was a Sufi of the tarekat Naqshabandîyah who held a duty as the mufti of the Deli Sultanate. His spiritual genealogy, unfortunately, has been an unrevealed mystery due to the absence of literatures which inform us the comprehensive biographies of his Sufi teachers. As the proponent of neo-sufisme, he authored a number of works in theology, fiqh, astronomy (falak), and mystical (tasawuf) disciplines. It has been known from his two mystical works that he combined sharî?ah, tarîqah, and haqîqah, and also emphasized the importance of obedience towards sharî?ah for mushrif and sâlik in order to achieve ?the pearl of Reality?.